Electrospun TiO2 electrodes for dye-sensitized solar cells - Song, MY; Kim, DK; Ihn, KJ; Jo, SM; Kim, DY (IOP PUBLISHING LTD, 2004)
We report the new application of electrospun TiO2 fibres as an electrode for dye-sensitized solar cells (DSSCs). TiO2 fibre electrode was electrospun directly onto a conducting glass substrate from a mixture of titanium(IV) propoxide and poly(vinyl acetate) (PVAc) in dimethyl formamide. The TiO2 fibres are composed of one-dimensionally aligned nanofibrils about 20 nm thick with an islands-in-a-sea morphology, which was obtained from the phase separation of TiO2 gel and PVAc during the solidification process. The porous structure of the electrospun TiO2 electrode was found to be efficiently penetrated by a viscous polymer gel electrolyte. In order to improve the photocurrent generation, we treated the electrospun TiO2 electrode with TiCl4 aqueous solution. The rutile crystal was grown on the surface of anatase TiO2 fibres. An additional TiO2 layer increased the volume fraction of active materials, resulting in an increase of sensitizer adsorption. The energy conversion efficiency obtained from electrospun TiO2 electrodes with a PVDF-HFP gel electrolyte was over 90% of that from a liquid electrolyte system.